Photophysical studies of six amphiphilic 2:1 cyclodextrin:[60]fullerene derivatives - Quaranta, Annamaria; Zhang, Yongmin; Filippone, Salvatore; Yang, Juan; Sinay, Pierre; Rassat, Andre; Edge, Ruth; Navaratnam, Suppiah; McGarvey, David; Land, Edward; Brettreich, Michael; Hirsch, Andreas; et al. (Chemical Physics, 2006)
In search of a simple internal complexation of C in cyclodextrins, six 2:1 cyclodextrin:[60]fullerene conjugates involving different types of linkers have been synthesised. Using spectrophotometry, laser flash photolysis and pulse radiolysis, we have investigated spectroscopic and photophysical properties of these 2:1 cyclodextrin [60]fullerene monoadduct conjugates (CDF), including ground and triplet state absorption spectra, triplet molar absorption coefficients (ε), quantum yields of triplet (Φ) and singlet oxygen formation (Φ) in water and toluene, in order to probe the possibility of 2:1 inclusion complexes of C between two cyclodextrins. In water, the CDF spectroscopic and photophysical properties indicate hydrophobically driven self-assemblies of the amphiphilic conjugates into spherical micelles with no evidence for the presence of a 2:1 inclusion complex, while in toluene they show no sign of aggregation. It is observed that formation of aggregates in water does not prevent scavenging of HO radical by the C moiety of the CD-C conjugates. © 2006 Elsevier B.V. All rights reserved.